Florida Forage Handbook: Preface - Yoana Newman; Carroll G. Chambliss (EDIS)
This revised 2-page fact sheet introduces the new edition of the Florida Forage Handbook which has become the go-to-guide for every Florida forage enthusiast, new or seasoned, and now contains updated and expanded information most relevant to today's livestock producer and forage manager. Written by Y.C. Newman and C.G. Chambliss, and published by the UF Department of Agronomy, April 2011.